Effects of aging on abdominal wall healing in rats - Biondo-Simões,Maria de Lourdes Pessole (2005)
PURPOSE: The aim of this study was to assess abdominal wall healing in old and young adult rats. METHODS: On average, young animals were 110 days old and old animals were 762 days old. A 4.0 cm median laparotomy was performed under anesthesia, followed by laparorrhaphy on two synthesis planes, i.e. peritoneum-muscle-aponeurosis and skin, using continuous 5.0 nylon sutures. The animals were evaluated on the 3rd, 7th, 14th and 21st postoperative days. The resistance of the two planes was studied separately and a histopathologic analysis was performed on sections stained with hematoxylin-eosin and Sirius Red. Immunohistochemical analysis was also carried out using PCNA, LCA and CD34. RESULTS: The skin scars gained resistance in a similar manner at the initial time points, but those of young rats were more resistant on the 21st day (p=0.0029). Total and type III collagen content was similar in the two groups and type I collagen content was higher in young animals on the 14th day. Inflammatory cell infiltration was more marked in the skin wounds of young animals on the 3rd day (p=0.0190). Reepithelialization was similar and angiogenesis was more intense in the skin wounds of young animals on the 14th day (p=0.0062). The peritoneum-muscle-aponeurosis wounds gained similar resistance during the early phases, but were more resistant on the 14th day (p=0.0005) and on the 21st day (p=0.0023) in old rats Collagen concentration was higher in the wounds of old animals on the 3rd day (p=0.0112) and in the wounds of young animals on the 21st day (p=0.0348). The inflammatory reaction was more intense in the wounds of old animals on the 3rd day (p=0.0060) and angiogenesis was more intense on the 14th day (0.0432). CONCLUSION: Although there are some differences in the healing course between young and old animals, age, of itself, does not impair the healing of abdominal wall wounds in rats.